Pronounced peramorphosis in lissamphibians--Aviturus exsecratus (Urodela, Cryptobranchidae) from the Paleocene-Eocene Thermal Maximum of Mongolia. - Davit Vasilyan; Madelaine Böhme (PLoS ONE, 2012)
BACKGROUND: The oldest and largest member of giant salamanders (Cryptobranchidae) Aviturus exsecratus appears in the latest Paleocene (near the Paleocene-Eocene Thermal Maximum) of Mongolia. Based on femoral and vertebral morphology and metrics, a terrestrial adaptation has been supposed for this species. METHODOLOGY/PRINCIPAL FINDINGS: A detailed morphological reinvestigation of published as well as unpublished material reveals that this salamander shows a vomerine dentition that is posteriorly shifted and arranged in a zigzag pattern, a strongly developed olfactory region within the cranial cavity, and the highest bone ossification and relatively longest femur among all fossil and recent cryptobranchids. CONCLUSIONS/SIGNIFICANCE: The presence of these characteristics indicates a peramorphic developmental pattern for Aviturus exsecratus. Our results from Av. exsecratus indicate for the first time pronounced peramorphosis within a crown-group lissamphibian. Av. exsecratus represents a new developmental trajectory within both fossil and recent lissamphibian clades characterized by extended ontogeny and large body size, resembling the pattern known from late Paleozoic eryopines. Moreover, Av. exsecratus is not only a cryptobranchid with distinctive peramorphic characters, but also the first giant salamander with partially terrestrial (amphibious) lifestyle. The morphology of the vomers and dentaries suggests the ability of both underwater and terrestrial feeding.